A HISTORICAL SURVEY OF SOCIO-POLITICAL ADMINISTRATION IN AKURE REGION UP TO THE CONTEMPORARY PERIOD - Afe, Adedayo Emmanuel (European Scientific Journal, ESJ, 2012)
Thepaper examines the political transformation of Akureregion from the earliest times to the present. The paper traces these stages of political development in order to demonstrate features associated with each stage. It argues further that pre-colonial Akure region, like other Yoruba regions, had a workable political system headed by a monarch. However, the Native Authority Ordinance of 1916, which brought about the establishment of the Native Courts and British judicial administration in the region led to the decline in the political power of the traditional institution.Even after independence, the traditional political institution has continually been subjugated. The work relies on both oral and written sources, which were critically examined. The paper, therefore,argues that even with its present political status in the contemporary Nigerian politics, the traditional political institution is still relevant to the development of thesociety.